Making sense of test-based accountability in education - Hamilton, Laura S.; Stecher, Brian M.; Klein, Stephen P., 1938- (Rand, 2002)
Test-based accountability systems that attach high stakes to standardized test results in the form of rewards and sanctions have raised a number of issues for those responsible for educational assessment and accountability. Do these high-stakes tests measure student achievement accurately? How can policymakers and educators attach the right consequences to the results of these tests? What kinds of educational tradeoffs do these testing policies introduce? This book was written in response to school policymaking's growing emphasis on high-stakes testing. It addresses several key areas, including how the tests are used within these systems, how to evaluate the technical quality and trustworthiness of the tests, how test-based accountability affects the practices of teachers and schools, and what effect political considerations have on the policy debate. The authors also provide some recommendations for developing more-effective test-based accountability systems.